The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/economies6010007
|View full text |Cite
|
Sign up to set email alerts
|

Non-trivial Factors as Determinants of the Environmental Taxation Revenues in 27 EU Countries

Abstract: Abstract:The implementation of environmental taxation is one of the most important issues of environmental policy in Europe. To approach this matter, the paper aims to analyse the determinants of environmental taxation revenue for European countries. Besides investigating the most explored determinants, such as those related to production, consumption and environmental quality, particular attention is paid to some non-trivial factors. Firstly, we analyse the importance of the institutional context that is cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…With the context above, the existing studies have analyzed environmental tax from various perspectives, with focuses on the driver and linkage with other socioeconomic variables. For example, Castiglione et al (2018) showed that the determinants of ETR were different for different EU countries due to the institution and economic development by comparing three indices of environmental tax [ 8 ]. Further, Andreoni (2019) decomposed the change in ETR into three drivers by LMDI in EU countries and found that economic growth contributed to the increase in ETR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the context above, the existing studies have analyzed environmental tax from various perspectives, with focuses on the driver and linkage with other socioeconomic variables. For example, Castiglione et al (2018) showed that the determinants of ETR were different for different EU countries due to the institution and economic development by comparing three indices of environmental tax [ 8 ]. Further, Andreoni (2019) decomposed the change in ETR into three drivers by LMDI in EU countries and found that economic growth contributed to the increase in ETR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, unlike most previous studies focusing on driver of ETR over time [ 10 , 11 ], the study comprehensively investigated the spatiotemporal drivers of ETR by using temporal LMDI and newly developed spatials within and between LMDI approaches, simultaneously. Moreover, we conducted the study in the context of the largest developing country, China, which is different from most existing studies on the developed economy (see previous studies, [ 5 , 8 ], for example) and thus provides valuable insights on sustainable development for countries in transition, such as China in particular. Second, the study explored the long-term trend and complex network of ETR based on the newly developed convergence test and social network analysis, which have rarely been documented in the current literature (e.g., Andreoni (2019) and Castiglione et al (2018)) [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most recent examples is the accumulation of electric and electronic waste, which is the fastest growing waste stream of the planet (OECD, 2008). Exhausted by desperate living conditions, the local population earns by decomposing electrical and electronic waste in search of chemical components, that are sold in change for little money (Castiglione, Infante, & Smirnova, 2018). This mechanism works despite traditional respect for nature, whcih highlights the indisputable importance of economic welfare for environmental progress, inseparable from the enforcement of institutions.…”
Section: Acquisition Of Environmental Concernmentioning
confidence: 99%